Evaluation of permeability and bioavailability of a lead antileishmanial compound buparvaquone in animal models [RS1-441]. - Gantala Venkatesh, Gantala Venkatesh (2009)
Leishmaniasis merupakan suatu kumpulan penyakit parasit yang disebabkan oleh genus Leishmania yang kini adalah endemik di lapan puluh lapan negara.